2015
DOI: 10.1111/nmo.12606
|View full text |Cite
|
Sign up to set email alerts
|

Esophagogastric junction morphology is associated with a positive impedance‐pH monitoring in patients with GERD

Abstract: Increasing separation between LES and CD can cause a gradual and significant increase in reflux. EGJ morphology may be useful to estimate an abnormal impedance-pH testing in GERD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 30 publications
1
75
0
4
Order By: Relevance
“…The presence of hiatal hernia exposes patients to increased AET, TNR and to a more severe GERD pattern[43]. In literature in fact, is currently reported that at baseline hiatus hernia, LES resting pressure and length are significantly more compromised in patients with severe erosive reflux disease (ERD) and Barrett’s esophagus (BE) compared to those with mild erosions and non erosive reflux disease (NERD).…”
Section: Anatomical Factors: Hiatal Hernia Presencementioning
confidence: 99%
“…The presence of hiatal hernia exposes patients to increased AET, TNR and to a more severe GERD pattern[43]. In literature in fact, is currently reported that at baseline hiatus hernia, LES resting pressure and length are significantly more compromised in patients with severe erosive reflux disease (ERD) and Barrett’s esophagus (BE) compared to those with mild erosions and non erosive reflux disease (NERD).…”
Section: Anatomical Factors: Hiatal Hernia Presencementioning
confidence: 99%
“…A new HRM metric evaluating EGJ barrier function, the EGJ contractile integral, incorporates EGJ length and pressure amplitudes during all phases of respiration . When abnormal, this metric identifies EGJ hypotension association with unequivocally abnormal reflux testing . Second, esophageal body motor function is characterized using software tools and defined according to Chicago Classification metrics into normal, fragmented peristalsis, ineffective esophageal motility, and absent contractility .…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing the PPI dose or receiving fundoplication was correlated with a low rate of BE recurrence after RFA. Some studies suggest that fundoplication may result in improved control of gastroesophageal reflux (acid, weakly acid, and weakly alkaline) and is associated with fewer recurrences of intestinal metaplasia after RFA in selected patients with a coexisting hiatal hernia of > 3 cm 83 or more severe reflux exposure …”
Section: Treatmentmentioning
confidence: 99%